2010
DOI: 10.1186/1753-2000-4-19
|View full text |Cite
|
Sign up to set email alerts
|

German Screen for Child Anxiety Related Emotional Disorders (SCARED): Reliability, Validity, and Cross-Informant Agreement in a Clinical Sample

Abstract: BackgroundThe psychometric properties and cross-informant agreement of a German translation of the Screen for Child Anxiety Related Emotional Disorders (SCARED) were assessed in a clinical sampleMethods102 children and adolescents in outpatient psychotherapy and their parents filled out the SCARED and Youth Self Report/Child Behaviour Checklist (YSR/CBCL).ResultsThe German SCARED showed good internal consistency for both parent and self-report version, and proved to be convergently and discriminantly valid whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 27 publications
(48 reference statements)
2
32
0
2
Order By: Relevance
“…While studies have largely confirmed the SCARED’s psychometric properties in clinically referred samples (Bodden, Bogels, & Muris, 2009; Dirks et al, 2014; Hariz et al, 2013; Monga et al, 2000; Muris, Dreessen, Bogels, Weckx, & van Melick, 2004; Muris & Steerneman, 2001; Stevanovic, 2012; Weitkamp, Romer, Rosenthal, Wiegand-Grefe, & Daniels, 2010), fewer have compared accuracy of diagnostic cutoffs obtained from the SCARED with diagnoses from standardized clinical interviews (Bodden et al, 2009; Gardner, Lucas, Kolko, & Campo, 2007; Hariz et al, 2013; Monga et al, 2000; Muris et al, 2004; Muris & Steerneman, 2001; Weitkamp et al, 2010). Among such studies, modest sample size has largely prohibited tests of discriminant validity between specific subtypes of anxiety disorder diagnoses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While studies have largely confirmed the SCARED’s psychometric properties in clinically referred samples (Bodden, Bogels, & Muris, 2009; Dirks et al, 2014; Hariz et al, 2013; Monga et al, 2000; Muris, Dreessen, Bogels, Weckx, & van Melick, 2004; Muris & Steerneman, 2001; Stevanovic, 2012; Weitkamp, Romer, Rosenthal, Wiegand-Grefe, & Daniels, 2010), fewer have compared accuracy of diagnostic cutoffs obtained from the SCARED with diagnoses from standardized clinical interviews (Bodden et al, 2009; Gardner, Lucas, Kolko, & Campo, 2007; Hariz et al, 2013; Monga et al, 2000; Muris et al, 2004; Muris & Steerneman, 2001; Weitkamp et al, 2010). Among such studies, modest sample size has largely prohibited tests of discriminant validity between specific subtypes of anxiety disorder diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, correlational analyses typically yield only modest levels of informant agreement (Birmaher et al, 1999; Birmaher et al, 1997; Cosi et al, 2010; Muris, Merckelbach, van Brakel, & Mayer, 1999; Su et al, 2008; Weitkamp et al, 2010). From a clinical perspective, it is critical to determine if informants provide complementary information that improves accuracy of clinical cutoffs, or if informant discrepancies lead to diagnostic discrepancies that vary based on the informant (Klein, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The parent and child versions of the SCARED (Birmaher et al, , 1999Hale et al, 2005;Monga et al, 2000) are 41-item self-report questionnaires measuring symptoms of DSM-IV defined anxiety disorders except for obsessive-compulsive disorder. It is available in multiple languages (e.g., German, Italian, and Chinese) and has been used in different cultures (Su et al, 2008;Weitkamp et al, 2010). Administration time is * 10 min.…”
Section: Psychiatric and Psychological Functioningmentioning
confidence: 99%
“…In einer ersten Prüfung der deutschen Version an einer Feldstichprobe zeigten sich ebenfalls gute psychometrische Qualitäten: Die Kinderversion wurde an 556 Grundschulkindern im Alter von 8 bis 12 Jahren validiert. Das Selbsturteil des SCARED wies eine gute interne Konsistenz auf (Gesamtwert: α = .91, Subskalen: α = .66 bis α = .81; Essau, Muris, Ederer, 2002), ebenso das Elternurteil bei klinisch auffälligen Kindern und Jugendlichen (Gesamtwert: α = .90, Subskalen: α = .80 bis α = .92; Weitkamp, Romer, Rosenthal, Wiegand-Grefe, Daniels, 2010). Lediglich die Skala Trennungsangst im Elternurteil hatte ein nicht zufriedenstellendes α = .51.…”
Section: Hintergrundunclassified